Hubungan Tingkat Partisipasi Laki-Laki dengan Tingkat Keberdayaan Ekonomi Perempuan - Taufiqurrahman, Fahmi; Sumarti, Titik; Falatehan, Sriwulan Ferindian (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
ABSTRACTWorld Bank Survey shows that 42,8% of formal SMEs are owned by women and 43% of formal SMEs in Indonesia also belong to women with a contribution of 9,1% to Indonesia’s GDP in 2013. Looking at the facts, the improvement of women’s economic empowerment becomes important in order to strengthen women’s bargaining position in the public sector. Although the program is aimed for women, in practice required the participation of men in supporting women’s economic empowerment in order to run balanced development. The purposes of this research are: (1) to identify factors affecting the level of men’s participation in supporting the economic activities of women, (2) to analyze the level of men’s participation, (3) to analyze the correlation between factors affecting the level of men’s participation with the level of men’s participation, (4) to analyze the economic empowerment level of women, (5) to analyze the correlation between the level of men’s participation with the economic empowerment level of women. The method used in this research is a survey method using a questionnaire to 35 respondents who are husbands of women Kharisma cooperative members who have business. The results from this research shows: (1) the factors that affecting men’s participation are type of work, the income level, the education level, and the age of marriage, (2) the level of men’s participation at medium level (tokenism), (3) there isn’t significant correlation between factors that affecting level of participation with the level of men’s participation, (4) the level of women’s economic empowerment at the high level and, (5) there is a significant correlation between the level of men’s participation with the level of women’s economic empowerment.Keywords : Gender, participation, women’s empowerment—————————- ABSTRAKSurvei yang dilakukan oleh Bank Dunia menunjukan sebanyak 42,8% UKM formal dimiliki oleh perempuan dan sebanyak 43% UKM formal di Indonesia juga milik perempuan dengan kontribusi sebesar 9,1% terhadap PDB Indonesia pada tahun 2013. Melihat fakta tersebut, peningkatan pemberdayaan ekonomi perempuan menjadi penting demi memperkuat bargaining position perempuan di sektor publik. Meskipun ditujukan untuk perempuan, dalam pelaksanaannya dibutuhkan partisipasi laki-laki dalam mendukung keberdayaan ekonomi perempuan agar pembangunan berjalan seimbang. Penelitian ini bertujuan untuk: (1) mengidentifikasi faktor-faktor yang mempengaruhi tingkat partisipasi laki-laki, (2) mengidentifikasi tingkat partisipasi laki-laki, (3) menganalisis hubungan antara faktor-faktor yang mempengaruhi partisipasi laki-laki dengan tingkat partisipasi laki-laki, (4) mengidentifikasi tingkat keberdayaan ekonomi perempuan, (5) menganalisis hubungan antara tingkat partisipasi laki-laki dengan tingkat keberdayaan ekonomi perempuan. Metode yang digunakan dalam penelitian ini adalah metode survei dengan menggunakan kuesioner kepada 35 responden yang merupakan suami dari perempuan anggota koperasi Kharisma yang memiliki usaha. Hasil penelitian ini menunjukkan (1) faktor-faktor yang mempengaruhi tingkat partisipasi laki-laki antara lain umur, jenis pekerjaan, tingkat pendapatan, tingkat pendidikan, dan lama perkawinan, (2) tingkat partisipasi laki-laki di Desa Sudajaya Girang termasuk ke dalam tingkat partisipasi sedang (tokenisme), (3) terdapat hubungan yang tidak signifikan antara faktor-faktor yang mempengaruhi partisipasi dengan tingkat partisipasi laki-laki, (4) tingkat keberdayaan ekonomi perempuan anggota koperasi tergolong tinggi, dan (5) terdapat hubungan yang signifikan antara tingkat partisipasi laki-laki dengan tingkat keberdayaan ekonomi perempuan.Kata Kunci : Gender, partisipasi, pemberdayaan perempuan